Specific protein phosphorylation in interferon-treated uninfected and virus-infected mouse L929 cells: enhancement by double-stranded RNA. - Gupta, S L (1979)
The enhanced phosphorylation of specific protein(s) observed in extracts from interferon-treated cells (in the presence of ATP and double-stranded [ds] RNA) was also seen in intact mouse L929 cells upon treatment with dsRNA, polyriboinosinic.polyribocytidylic acid [poly(rI.rC)] or reovirus dsRNA, using 32Pi as radiolabel. Labeling of a 65,000-dalton protein(s) with 32P was greatly increased in interferon-treated cells in the presence of added dsRNA, suggesting that the expression in vivo of the kinase activity involved is regulated by dsRNA. This was used as a test system to investigate whether the activity of interferon-induced enzyme(s) is stimulated following virus infection, possibly owing to the accumulation of dsRNA. No obvious increase in 32P-labeling of 65,000-dalton protein(s) was observed upon infection of interferon-treated cells with mengovirus or vesicular stomatitis virus. A basal level of 32P-labeling of the 65,000-dalton protein(s) was detected in interferon-treated cells in the absence of added dsRNA, indicating a basal level of expression of the kinase activity involved. The possible implications of these results are discussed.